2018
DOI: 10.1007/s10880-018-9554-y
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Young Adults Living with Congenital Heart Disease: Coping, Stress Reactivity, and Emotional Functioning

Abstract: Living with congenital heart disease (CHD) presents survivors with numerous stressors, which may contribute to emotional problems. This study examined (a) whether coping with CHD-related stress predicts symptoms of depression and anxiety, and (b) whether associations between coping and emotional distress are moderated by involuntary stress reactivity. Adolescents and young adults diagnosed with CHD (M = 26.4) were recruited from pediatric and adult outpatient cardiology clinics. Participants (N = 168) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Accordingly, encountering a negatively appraised situation may trigger poor adaptive responses that can create barriers to finding effective solutions to problems. Altogether, this situation can lead to the adoption of ineffective coping strategies and, in turn, an increase in anxiety [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, encountering a negatively appraised situation may trigger poor adaptive responses that can create barriers to finding effective solutions to problems. Altogether, this situation can lead to the adoption of ineffective coping strategies and, in turn, an increase in anxiety [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…If the assessment of a situation is negative and the person lacks the means to deal with it, a stress response associated with physical, psychological, and even emotional symptoms may be triggered. This response leads to a less effective coping style [18]. Clark and Beck [19] concluded that coping strategies often play a significant role in the ongoing presence of disorders such as anxiety and are consistent with latent schematic content and cognitive vulnerability.…”
Section: Anxiety and Copingmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9,[28][29][30][31][32][33] These difficulties may result in the child or adolescent with congenital heart disease having more behavioural and emotional problems, worse self-perception, social isolation, and school difficulties, as well as a greater need for academic, therapeutic, and psychosocial/psychiatric supports. 5,9,[34][35][36][37][38][39][40] By adolescence, one-third to one-half of survivors of neonatal and infant surgery have required special services in school, 7-15% have been placed in substantially separate classrooms, and~18% have repeated a grade. [30][31][32][33] With transition to adulthood, neurocognitive and behavioural disabilities can impact employability, the ability to form meaningful peer relationships, mental health, and health-related quality of life.…”
mentioning
confidence: 99%
“…Studies that include young adults coping with a cardiac illness are scarce (McDonough, 2009 ; Wong et al, 2017 ). Systematic reviews interested in the psychosocial aspects of individuals coping with a cardiac illness do not specifically deal with young adults (Fredericks et al, 2012 ; Foxwell et al, 2013 ; Herr et al, 2014 ; Doyle et al, 2015 ; Li et al, 2015 ; Tully et al, 2015 ; Ooi et al, 2016 ; Le et al, 2018 ), and studies that do usually focus on patients coping with congenital heart diseases (Van Rijen et al, 2004 , 2005a , b ; Fredriksen et al, 2009 ; Asp et al, 2015 ; Uzark et al, 2015 , 2016 ; Jackson et al, 2017 ; Abda et al, 2018 ; Andonian et al, 2018 ; Grady et al, 2018 ; Monti et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%